2019
DOI: 10.1093/infdis/jiz417
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Antigen-Specific T-Cell Responses During the First 6 Months of Antiretroviral Treatment

Abstract: The reconstitution of Mycobacterium tuberculosis antigen-specific CD4 T cells in a cohort of HIV-infected persons starting antiretroviral treatment (ART) in a high tuberculosis endemic area is described. Restoration of the antigen-specific CD4 T-cell subsets mirrored the overall CD4 T-cell compartment. Activation (assessed by HLA-DR expression) decreased during ART but remained elevated compared to HIV-uninfected persons. Despite known M. tuberculosis sensitization determined by interferon-γ release assay, 12/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 15 publications
10
12
0
Order By: Relevance
“…Our more targeted analysis of soluble plasma biomarkers in the context of Mtb sensitisation during ART, using QFT supernatants, shows a decrease in antigen specific IL-beta and IL-1alpha as well as MCP-1, in line with decreased HIV-1 induced immune activation and inflammation. At the same time, antigen specific IP-10 (Ag-nil) concentrations significantly increased, together with chemokine expressing CD4 T cells, in keeping with memory T cell expansion as we demonstrated previously (7, 10). Overall, our data indicates that the ART- induced decrease in immune activation combined with improved antigen responsiveness may contribute to reduced susceptibility to tuberculosis in HIV-1-TB co-infected persons.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our more targeted analysis of soluble plasma biomarkers in the context of Mtb sensitisation during ART, using QFT supernatants, shows a decrease in antigen specific IL-beta and IL-1alpha as well as MCP-1, in line with decreased HIV-1 induced immune activation and inflammation. At the same time, antigen specific IP-10 (Ag-nil) concentrations significantly increased, together with chemokine expressing CD4 T cells, in keeping with memory T cell expansion as we demonstrated previously (7, 10). Overall, our data indicates that the ART- induced decrease in immune activation combined with improved antigen responsiveness may contribute to reduced susceptibility to tuberculosis in HIV-1-TB co-infected persons.…”
Section: Discussionsupporting
confidence: 87%
“…Overall, the above data support a decrease in HIV-1 induced immune activation and inflammation over the first 6 months of ART, even in the context of Mtb sensitisation. However, to better understand the increase in antigen specific IP-10 (Ag-Nil) concentrations, we evaluated the expression of chemokine receptors CXCR3, CCR4 and CCR6 on the surface of CD4 T cells, using PBMC in a subset of 25 patients from the same cohort, as previously described (10). We found expanding numbers of CD4 T cells expressing CXCR3 (the receptor for IP-10), as well as Due to increased rates of cardiovascular disease among people living with HIV-1, this is an important area to explore in further studies.…”
Section: Chemokine Receptor Analysis Using Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Immune reconstitution was key since we based the HITTIN phenotype on immune assays which are dependent on functioning T-cells. The ability of ART reconstituted CD4 T-cells to produce IFN-γ in response to ESAT-6/CFP-10 remains the same or improves with time on ART, although this is not always fully restored to the same extent as in HIV uninfected persons [35] , [36] , [37] , [38] . Although the ART duration in HITTIN was shorter than that of HIT and previous TB groups, it has been determined that the functional potential of Mtb -antigen specific T-cells can significantly change after only three months on ART [36] .…”
Section: Discussionmentioning
confidence: 97%
“…The ability of ART reconstituted CD4 T-cells to produce IFN-γ in response to ESAT-6/CFP-10 remains the same or improves with time on ART, although this is not always fully restored to the same extent as in HIV uninfected persons. [35][36][37][38] Although the ART duration in HITTIN was shorter than that of HIT and previous TB groups, it has been determined that the functional potential of Mtb-antigen specific T-cells can significantly change after only three months on ART. [36] Most studies considered the effect of ART over only a few weeks, but HITTIN identified in this study have been on ART an average of 7 years, making it unlikely that the negative results in IGRA and TST reported here are due to a lack of host ability to produce IFN-γ.…”
Section: Discussionmentioning
confidence: 99%